Effects of Therapeutic Hypothermia Initiated After 6 Hours of Age on Death or Disability Among Newborns With Hypoxic-ischemic Encephalopathy. Issue 3 (September 2018) - Laptook, A.R.; Shankaran, S.; Tyson, J.E.; Munoz, B.; Bell, E.F.; Goldberg, R.N.; Parikh, N.A.; Ambalavanan, N.; Pedroza, C.; Pappas, A.; Das, A.; Chaudhary, A.S.; et al.
Abstract : ( JAMA 2017;318(16):1550–1560) Previous trials have shown therapeutic hypothermia reduces death or disability when infants with hypoxic-ischemic encephalopathy are treated within 6 hours after birth. Getting infants treated in this window can be difficult when transportation is necessary or when encephalopathy is not recognized within 6 hours. This study aimed to determine whether hypothermia treatment can reduce the risk of death or disability due to hypoxic-ischemic encephalopathy at 18 months when treatment is initiated between 6 and 24 hours after birth.